If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+10+2x=59
We move all terms to the left:
5x+10+2x-(59)=0
We add all the numbers together, and all the variables
7x-49=0
We move all terms containing x to the left, all other terms to the right
7x=49
x=49/7
x=7
| 12-4z=-20-4z | | 3x+4+56=180 | | 4j-6=3j | | 3(-9s+5)=-10s-6s-51 | | 0.3xx=6 | | 3r-7r=-8-5r | | z=4.1=9.6 | | 29/n=13 | | 8n+13=11n-8 | | 41 (20x−28)=13 | | 7(5x-4)-x=-14-8x | | 7c=8c-8 | | 6r-2r=5(1-r)+5(6r-1) | | a+2a+12=36 | | 1x=0-2 | | 15=4v-1-4 | | 18-n/9=8 | | 4x+24=2-6(x+3) | | 457+2x=409 | | -3x²+9x=-810 | | 6(x+1)+2=26 | | x^2+5,2x=78 | | 7+5x+x=37 | | 5x+x-6=2x+10 | | 5k+8=-42 | | -1+q=9-q | | 15=y−5 | | 5÷m=8 | | 201=104-u | | -4(r+9)=24 | | 3(23+x)=90 | | f(4)=-f(4)={4-7}+3 |